Recognition of Diversity, Inclusion, and Social Justice in Paralympic Sport - Arellano, Yaneth Del Carmen Caicedo; Muñoz, Ricardo Alonso Mendoza (Journal of Posthumanism, 2025)
This article aims to understand how diversity, inclusion and social justice are recognized in Paralympic athletes, based on their feelings, perceptions and descriptions, coaches and parents. In addition, it illustrates and invites us to reflect on the current situation of the Paralympic sports system, the problems it faces today and its boom in the future. The sample had 50 participants divided into three groups: active Paralympic athletes with cognitive, motor and sensory disability (30), coaches (10), parents (10). The data collection was carried out from September to November 2021 and a qualitative methodological design was applied, continuing with the hermeneutic approach where the reality of Paralympic athletes is understood, followed by an ethnographic method to obtain an analytical description. Another component of the methodology concerns the unit of analysis where a convenience sampling with selection criteria was carried out. Finally, the collection techniques and instruments that facilitated the data collection needed for this research will be shown. This article illustrates and invites us to reflect on the sporting processes, participation, acceptance, support, and accessibility that the Paralympic athlete faces today.